Konsep Kafaah dalam Segi Sosial dan Agama: Konsep kafaah segi agama dan sosial - Farabi, Muhammad Al (Maliki Interdisciplinary Journal, 2024)
This article discusses the concept of "Kafaah" (equivalence) in marriage according to various Islamic schools of thought, particularly the Hanbali, Maliki, and Hanafi schools. Kafaah encompasses important aspects such as religion, lineage, freedom, wealth, and health. Different schools have varying views on religious equivalence, with the Hanafi school emphasizing Muslim lineage, while other scholars assess equivalence based on piety. Lineage is considered significant, especially in the context of Arab descent, but Islam teaches that the distinction among people should be based on piety rather than race or tribe. Freedom is a crucial requirement, as a man must not be a slave to be considered equal. Financial capability to provide a dowry and maintenance is also a factor in equivalence, along with physical and mental health, as disabilities can affect compatibility. The article underscores the importance of harmony in the household and the role of guardians in determining the equivalence of prospective partners. It highlig hts that Kafaah is essential for ensuring compatibility and reducing conflicts in marriage, despite differing opinions among scholars regarding its importance and criteria.